EFFECT OF BALANCE COUNSELING STRATEGY TOWARDS KNOWLEDGE AND ATTITUDE IN CONTRACEPTION AMONG PREGNANT WOMEN - Alfi Syifa Darmastuti; Kasiati Kasiati; Muhammad Ardian Cahya Laksana; Linda Dewanti (Indonesian Midwifery and Health Sciences Journal, 2020)
Abstract Background: The use of postpartum contraception is ideally used after delivery under 42 days. Data obtained from the BKKBN of East Java Province, the achievement of unmet need in Surabaya is 13.31% of the unmet need target of 10.44%. The Balanced Counseling Strategy is a family planning counseling method that is practical, interactive, client-friendly, and encourages the client’s active participation. The purpose of this research is to know the effect of using BCS on improving the knowledge and attitudes of pregnant women about family planning. Method: In this quasy experimental research, pre-post with control group designed was implemented. Quota sampling is used to choose responden. Questionaire is used for research instrument. Data analysis used Paired t-test, Wilcoxon Signed Rank Test and Mann-Whitney Test. Results: Thirty nine of pregnant women are studied.  The intervention group has increased knowledge scored 16,64 (p-value = 0,003) though the control  group score 5.11 (p-value = 0,030) that is showed that there is significant different between two grups with p-value 0,045. The intervention group has increased attitudes scored 1,95 (p-value = 0,003) though the control  group 0,11 (p-value = 0,650) that is showed that there is significant different between two grups with p-value 0,015.  Conclusion: Counseling using Balanced Counseling Strategy can increase knowledge and attitude of pregnant women about family planning and more effective than pregnancy-class methods at Tanah Kalikedinding of Public Health 2019.